Social Information and Economic Decision-Making in the Ultimatum Game - Gaertig, Celia; Moser, Anna; Alguacil, Sonia; Ruz, María (Frontiers in Neuroscience, 2012)
The present study tested how social information about the proposer biases responders’ choices of accepting or rejecting real monetary offers in a classic ultimatum game and whether this impact is heightened by the uncertainty of the context. Participants in our study conducted a one-shot ultimatum game in which their responses had direct consequences on how much money they earned. We used trait-valenced words to provide information about the proposers’ personal characteristics. The results show higher acceptance rates for offers preceded by positive words than for those preceded by negative words. In addition, the impact of this information was higher in the uncertain than in the certain context. This suggests that when deciding whether or not to take money from someone, people take into account what they know about the person they are interacting with. Such non-rational bias is stronger in an uncertain context.